EFEKTIVITAS PEMBERIAN EDUKASI TERHADAP PENGETAHUAN IBU POST PARTUM TENTANG MENYUSUI DI BIDAN PRAKTEK MANDIRI PARTINI KECAMATAN PANTAI CERMIN KABUPATEN SERDANG BEDAGAI TAHUN 2023 - Rapida Saragih; Ida Lestari Tampubolon (Jurnal Maternitas Kebidanan, 2023)
Milk (ASI) is a source of nutrients that can be beneficial for the health of mothers and children. Breastfeeding is very important, especially in the early stages of life; thus, it is sufficient for newborns to be given only breast milk for the first 6 months. This study aims to determine the effectiveness of providing education on the knowledge of post partum mothers about breastfeeding at the Tanjung Beringin Health Center, Hinai District, Langkat Regency in 2022. The research method used The type of research used was quasi-experimental research with the research design used was one group pre test-post test design. The research location was conducted at the Tanjung Beringin Health Center, Hinai District, Langkat Regency. The time of the study was July-October 2022. The samples in this study were all post partum mothers who came to the Tanjung Beringin Health Center, totaling 30 respondents. The sample used was purposive sampling. The research instrument is a questionnaire that has been tested for validity and reliability. The results showed that 30 respondents had statistical test results using the paired t test where the results of the pre-test and post-test descriptive statistical research proved to be higher in the post-test. It can be concluded that the effectiveness of providing education can increase knowledge of breastfeeding. The conclusion that can be obtained is that knowledge with the effectiveness of providing education after treatment can increase respondents' knowledge about breastfeeding at the Tanjung Beringin Health Center, Hinai District, Langka Regency in 2022. It is suggested that this research will add information in the development of science, especially in obstetrics in studying the importance of breastfeeding Key words: Effectiveness of Providing Education, Knowledge